Analog performance of GaN/AlGaN high-electron-mobility transistors - de Oliveira Bergamim, Luis Felipe [UNESP] (2021)
In this paper, the analog properties of advanced GaN/AlGaN High-Electron-Mobility Transistors (HEMTs) are studied as a function of temperature (T). The drain current, the threshold voltage, the transconductance and the output conductance are experimentally investigated under saturation operation. Moreover, important figures of merit for the analog performance, such as transconductance-over-drain current, Early voltage and intrinsic voltage gain are analyzed for different channel lengths in the temperature range of 25 °C till 200 °C. The results indicate that due to change in the Fermi potential, the analog parameters reduce with increasing T. Furthermore, the performance increase for longer channel devices is correlated directly with the lower drain electric field penetration.